An improved nonlinear analytical approach to generate fragility curves of reinforced concrete columns subjected to blast loads. Issue 3 (February 2018) - Yu, Runqing; Chen, Li; Fang, Qin; Huan, Yi
Fragility curve is an efficient tool that is usually used to predict the failure probability of engineering structures in the damage assessment. To generate fragility curves for reinforced concrete columns under blast loads, a deterministic nonlinear analytical approach was first modified to consider the parameter uncertainties in materials, dimensions, and bearded loads. Monte Carlo simulation was applied to generate the corresponding fragility curves on the basis of the proposed approach. Damage of a typical reinforced concrete column under blast loads was assessed with the generated fragility curves. It was concluded that besides the standoff distance and equivalent trinitrotoluene charge, the axial force also significantly affected the damage of reinforced concrete columns under blast loads, especially in the moderate and large scaled distance.